Regenerative Endodontic Treatment of a Maxillary Mature Premolar - Qingan Xu; Zhou Li (Case Reports in Dentistry)
Regenerative endodontic treatment was performed on a mature maxillary premolar diagnosed as chronic pulpitis. The root canals were chemomechanically prepared and placed intracanal medicaments at the first appointment. Then 2 weeks later, a blood clot was created in the canals, over which mineral trioxide aggregate was placed. At 6-month follow-up, cementum-like tissue seemed to be formed in the root canal along with nearly recovered pulp vitality. At 12-month recall, the radiographic results revealed evidence of root wall thickening. At 30-month recall, no periapical lesion was found. This case report indicates that regenerative endodontic treatment for the mature premolar is feasible. More cases are needed for further validation.